2017
DOI: 10.1136/jmedgenet-2017-104669
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of genotype–phenotype correlations in Gorlin syndrome

Abstract: We propose that the clinical heterogeneity of GS can in part be explained by the underlying or variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 37 publications
4
96
1
8
Order By: Relevance
“…We investigated whether there were any genotype–phenotype relationships with PTCH1 mutations by gene domains or mutation type. Consistent with previous reports (Evans et al, ; Ikemoto et al, ; Kato et al, ; Okamoto et al, ), we found no hot spots or strong genotype–phenotype relationships. There was a suggestive association between falx cerebri calcifications and all transmembrane domains, although not statistically significant using a more conservative Bonferroni correction for multiple comparison.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We investigated whether there were any genotype–phenotype relationships with PTCH1 mutations by gene domains or mutation type. Consistent with previous reports (Evans et al, ; Ikemoto et al, ; Kato et al, ; Okamoto et al, ), we found no hot spots or strong genotype–phenotype relationships. There was a suggestive association between falx cerebri calcifications and all transmembrane domains, although not statistically significant using a more conservative Bonferroni correction for multiple comparison.…”
Section: Discussionsupporting
confidence: 93%
“…Germline mutations in two other genes, SUFU (OMIM 607035) and PTCH2 (OMIM 603673), have also been reported to cause rare cases of NBCCS. Both genes are negative regulators of the SHH pathway (Bresler et al, 2016;Evans et al, 2017;Fan et al, 2008;Fujii et al, 2013;Pastorino et al, 2009;Rimkus et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No association between the genetic variant and phenotype of this disease has been observed. Exons 2 to 21 were evenly distributed, and no clear hotspots were observed [ 27 , 28 ]. The most common form of mutation is frameshift mutation, followed by nonsense mutation, leading to the premature termination of PTCH1 translation ( Table S1 ).…”
Section: Genetic and Molecular Structural Aspects Of Gorlin Syndromentioning
confidence: 99%
“…The genotype-phenotype correlation is difficult to establish for NBCCS. Patients with SUFU mutation were significantly more likely to develop a medulloblastoma than those with PTCH1 mutations; however, they were less likely to develop odontogenic keratocysts [Evans et al, 2017].…”
mentioning
confidence: 93%